2014
DOI: 10.1101/008136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome sequencing of the perciform fishLarimichthys croceaprovides insights into stress adaptation

Abstract: 1The large yellow croaker Larimichthys crocea (L. crocea) is one of the most economically

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
(91 reference statements)
0
1
1
Order By: Relevance
“…Furthermore, some studies have identified a fourth type of olfactory-related receptor for formylated peptides, termed FPR and expressed in mammals (Rivière et al, 2009). However, we did not identity this gene family in the olfactory epithelium transcriptome of silver pomfret, and there are no reports about this receptor gene in other fish such as large yellow croaker (Ao et al, 2015). From the aspect of evolution, the absence of this gene family in fish may be attributable to the water solubility of formylated peptides.…”
Section: Olfactory-related Receptors For Amino Acids In Silver Pomfretcontrasting
confidence: 56%
“…Furthermore, some studies have identified a fourth type of olfactory-related receptor for formylated peptides, termed FPR and expressed in mammals (Rivière et al, 2009). However, we did not identity this gene family in the olfactory epithelium transcriptome of silver pomfret, and there are no reports about this receptor gene in other fish such as large yellow croaker (Ao et al, 2015). From the aspect of evolution, the absence of this gene family in fish may be attributable to the water solubility of formylated peptides.…”
Section: Olfactory-related Receptors For Amino Acids In Silver Pomfretcontrasting
confidence: 56%
“…In pace with the development of high-throughput sequencing technology, fish genome data have increased exponentially. So far, genomes of nearly 100 of fish species have been sequenced, including the genomes of Cynoglossus semilaevis (Chen et al 2014), Cyprinus carpio (Xu et al 2014), Larimichthys crocea (Ao et al 2015), Hippocampus comes (Lin et al 2016) and Ctenopharyngodon idellus (Wang et al 2015). These extensive genome data sets and the availability of genome editing technologies make it possible to decipher the functional genes in many fish species for both science and applications.…”
Section: Introductionmentioning
confidence: 99%